2013
DOI: 10.1111/jam.12155
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated fatty acid aerobic synthesis inBradyrhizobiumTAL1000 peanut-nodulating is affected by temperature

Abstract: Aims The aim of this work was to clarify the mechanism of monounsaturated fatty acid (MUFA) synthesis in Bradyrhizobium TAL1000 and the effect of high temperature on this process. Methods and Results Bradyrhizobium TAL1000 was exposed to a high growth temperature and heat shock, and fatty acid composition and synthesis were tested. To determine the presence of a possible desaturase, a gene was identify and overexpressed in Escherichia coli. The desaturase expression was detected by RT‐PCR and Western blotting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…High contents of iso-C 15:0 and anteiso fatty acids are characteristic of Gram positive bacteria, and dominance of odd numbered branched chain fatty acids in Micrococcus shows agreement with previous findings (Kaur et al 2005) Similar to our findings, accumulation of saturated fatty acids and a declined level of unsaturated fatty acid content with increasing temperature has been reported in several other groups of organisms (Denich et al 2003;Canion et al 2013). It has been found that temperature not only affects the activity of fatty acid desaturates, but also affects the formation and availability of primers required for biosynthesis of fatty acids, and consequently affects the membrane fluidity and stability (Paulucci et al 2013). Increased saturation and chain length with increasing temperatures and accumulation of short-chain, unsaturated and branched-chain fatty acids at lower temperatures are in fact essential to maintain the homeoviscous adaptation of the membrane during temperature stress (Sinensky 1974;Chihib et al 2003;Mrozik et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…High contents of iso-C 15:0 and anteiso fatty acids are characteristic of Gram positive bacteria, and dominance of odd numbered branched chain fatty acids in Micrococcus shows agreement with previous findings (Kaur et al 2005) Similar to our findings, accumulation of saturated fatty acids and a declined level of unsaturated fatty acid content with increasing temperature has been reported in several other groups of organisms (Denich et al 2003;Canion et al 2013). It has been found that temperature not only affects the activity of fatty acid desaturates, but also affects the formation and availability of primers required for biosynthesis of fatty acids, and consequently affects the membrane fluidity and stability (Paulucci et al 2013). Increased saturation and chain length with increasing temperatures and accumulation of short-chain, unsaturated and branched-chain fatty acids at lower temperatures are in fact essential to maintain the homeoviscous adaptation of the membrane during temperature stress (Sinensky 1974;Chihib et al 2003;Mrozik et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, normal cellular function requires membrane lipid that are largely fluid and the bilayers of most organisms are entirely or mostly fluid at physiological temperatures (Paulucci et al . ). The fluidity of biological membranes may be modulated by metabolic regulation of lipid composition (Thompson ).…”
Section: Introductionmentioning
confidence: 97%
“…The primary lipid components of the bilayer are phospholipids (PL), with fatty acids (FAs) being the major component (Paulucci et al . ). The major membrane‐forming PL in bacteria are phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and cardiolipin (CL) (Denich et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations